2018
DOI: 10.3168/jds.2018-14500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inner teat morphology by using high-resolution ultrasound: Changes due to milking and establishment of measurement traits of the distal teat canal

Abstract: The teat canal is important in the defense against invading pathogens, but its functional features can be impeded by the milking process. The objective of our study was to compare teat morphology before and after a standard milking procedure using high-resolution ultrasonography. Tissue changes were determined by measuring inner traits of teat morphology: teat width, teat end width, teat cistern width, diameter of the lower and upper teat wall, teat canal length, and teat canal diameter. Additionally, 3 traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
1
23
1
Order By: Relevance
“…This range is supported by recent ultrasonographic studies of the teat canal that reported an overall average teat canal diameter of 1.9 mm (Klein et al, 2005) and average diameters of 1.24 to 1.53 mm, depending on DIM and milking system (Khol et al, 2006). These values, however, stand in contrast to those reported in 3 more recent studies that documented ranges of 0.66 to 0.78 mm (Szencziová et al, 2013), 1.09 to 1.11 mm (Strapák et al, 2017), and 0.99 to 1.22 (Martin et al, 2018), depending on the time of recording.…”
Section: Average Teat Canal Dimensionscontrasting
confidence: 96%
See 4 more Smart Citations
“…This range is supported by recent ultrasonographic studies of the teat canal that reported an overall average teat canal diameter of 1.9 mm (Klein et al, 2005) and average diameters of 1.24 to 1.53 mm, depending on DIM and milking system (Khol et al, 2006). These values, however, stand in contrast to those reported in 3 more recent studies that documented ranges of 0.66 to 0.78 mm (Szencziová et al, 2013), 1.09 to 1.11 mm (Strapák et al, 2017), and 0.99 to 1.22 (Martin et al, 2018), depending on the time of recording.…”
Section: Average Teat Canal Dimensionscontrasting
confidence: 96%
“…The findings of our study are consistent with those of Neijenhuis et al (2001a), who reported an average relative increase of 12% in TCL immediately after milking. Other researchers reported an average elongation of the TCL of 19% (Martin et al, 2018), 20.5 and 32.9% in front and hind teats, respectively (Strapák et al, 2017), 27% (Szencziová et al, 2013), and 30 to 41% (Paulrud et al, 2005). In contrast, teat canal diameters were not meaningfully different after machine milking at t0 (P ≥ 0.23).…”
Section: Changes In Teat Canal Dimensions During Machine Milkingmentioning
confidence: 95%
See 3 more Smart Citations